1996
DOI: 10.1042/bj3170065
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase and kinase activities possibly involved in exocytosis regulation in Paramecium tetraurelia

Abstract: In Paramecium tetraurelia cells synchronous exocytosis induced by aminoethyldextran (AED) is accompanied by an equally rapid dephosphorylation of a 63 kDa phosphoprotein (PP63) within 80 ms. In vivo, rephosphorylation occurs within a few seconds after AED triggering. In homogenates (P)P63 can be solubilized in all three phosphorylation states (phosphorylated, dephosphorylated and rephosphorylated) and thus tested in vitro. By using chelators of different divalent cations, de- and rephosphorylation of PP63 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
1
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 63 publications
2
51
1
2
Order By: Relevance
“…As reported earlier, we have enriched two protein kinases, casein kinase type II (CK) and cGMP-dependent kinase (PKG), from 100000g supernatants of Paramecium cell homogenates which are able to phosphorylate PP63/pf in vitro (12). The scope of this study was to determine whether one of these kinases is involved in the reversible phosphorylation cycle of PP63/pf during regulated exo-and endocytosis in vivo.…”
Section: Biochemical Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As reported earlier, we have enriched two protein kinases, casein kinase type II (CK) and cGMP-dependent kinase (PKG), from 100000g supernatants of Paramecium cell homogenates which are able to phosphorylate PP63/pf in vitro (12). The scope of this study was to determine whether one of these kinases is involved in the reversible phosphorylation cycle of PP63/pf during regulated exo-and endocytosis in vivo.…”
Section: Biochemical Resultsmentioning
confidence: 99%
“…All solvents were of the highest quality available. Materials for isolation of protein kinases and for in vivo and in vitro phosphorylation studies were as reported previously (12).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations